A European peace facility could make a pragmatic contribution to peacebuilding around the world - Mark Furness; Julian Bergmann (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
The question of how the EU should finance peacebuilding in developing countries has challenged policy-makers and pundits for many years. At one level this is a technical and legal issue of budget lines and financing rules. It nevertheless touches on the much deeper political and even moral issues of whether the EU should use development aid to finance security provision, how best the EU can respond to the legitimate needs of partners in conflict-affected countries and what kind of civil and/or military engagements the EU can support as part of its external relations. The question has come to resemble the proverbial can being kicked along the road by successive European Commissioners, Council working groups and parliamentary committees. It has come to a head again because intra-EU negotiations for the next Multiannual Financial Framework for 2021-2027 are starting in earnest. This time, a sensible proposal is on the table which can potentially provide a pragmatic and workable solution, at least for a while. In December 2017, the European Council requested the Foreign Affairs Council to adopt a recommendation on a dedicated instrument for Capacity Building in Support of Security and Development (CBSD) for the post-2020 EU budget by the spring of 2018. In this context, the High Representative (HR) of the EU for Foreign and Security Affairs, Federica Mogherini, proposed that the EU create a European Peace Facility (EPF). While she did not provide any details, the general idea is that the EPF would be an `off-budget' fund to finance peace support operations and the capacity building of partner countries' security sectors. The fact that HR Mogherini's proposal sounds similar to another EU peacebuilding instrument – the African Peace Facility (APF) – is no accident. It is precisely due to problems experienced by the APF that the EPF is needed. Chief among these is the need to be able to provide stable, predictable funding to the African Union's peacebuilding activities and peacekeeping missions. This has proved more difficult than it should have been because of a second problem: the legal restrictions on financing military activities from the EU's budget. Overcoming this dilemma is only possible through an off-budget instrument which can meet the legitimate requirement of financing peace support operations while respecting one of the EU's core principles. The design of such an instrument presents political, legal and technical challenges for the EU's decision-makers. The most promising model for the EPF is to set it up as a multi-donor trust fund, open for direct contributions from member states. This model has the advantages of flexibility regarding EU budget rules, additionality (it could finance a mixture of Official Development Assistance (ODA) and non-ODA eligible expenses, rather than diverting aid to security activities) and visibility, since the EPF can be a global instrument based on the proven logic of the APF. The model has disadvantages as well, particularly that in the current crisis-driven climate there is strong pressure to use this kind of instrument for protecting Europe against real or perceived threats, such as terrorism or irregular migration. Some member states, and even parts of the Commission and EEAS, are highly likely to try to exempt the EPF from oversight by the European Parliament. The governance of the instrument is crucial, if it is to fulfil its mission of supporting developing countries' efforts to provide a secure basis for development.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Sicherheit; Frieden und fragile Staaten